2013
DOI: 10.1177/1082013212442193
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of Treixadura musts with autochthonousSaccharomyces cerevisiaestrains: Fermentative performance and influence on the wine characteristics

Abstract: The fermentative ability of five autochthonous Saccharomyces cerevisiae strains (XG1, XG2, XG3, XG4 and XG5) and their influence on the chemical composition and sensory properties of Treixadura wines were evaluated. The inoculated strains have successfully led and completed the fermentations. Wines obtained from different yeasts showed significant differences in total and volatile acidity. Regarding volatile compounds, significant differences among wines were found for acetates, ethyl esters, acetoin, 1-hexano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…The fact that ester composition of wines is strain dependent has been reported . In particular, the influence of yeast strains on ester composition of wine was studied for Albariño, and recently for Treixadura wines . Our results confirmed those findings, especially with strain XG3, which produced wines with the highest content of ethyl esters for both cultivars, Albariño and Godello.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The fact that ester composition of wines is strain dependent has been reported . In particular, the influence of yeast strains on ester composition of wine was studied for Albariño, and recently for Treixadura wines . Our results confirmed those findings, especially with strain XG3, which produced wines with the highest content of ethyl esters for both cultivars, Albariño and Godello.…”
Section: Resultssupporting
confidence: 85%
“…C6–C12 fatty acids content of Godello wines was higher in spontaneous fermentation and with XG3. Lower amounts of C4–C5 fatty acids in wines from spontaneous fermentations compared to wines fermented with local yeasts have been also found for Treixadura cultivar …”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…'Godello' provides intense taste to wines, but it possesses a lower aromatic potential than 'Albariño' (Versini et al, 1994). 'Treixadura' is one of the most important white grapevine cultivars in Galicia (Blanco et al, 2012). It is aromatic, giving fruity, floral and balsamic notes to the wines.…”
mentioning
confidence: 99%
“…However, tasters did not gave different marks for global quality to wines from any of the treatments. This indicates that the chemical differences observed were not enough to be detected at the sensory level as reported in a former study (Blanco et al, 2012), where panelists were not able to found noticeable differences in wine mouth attributes for 'Treixadura' wines fermented with different yeasts.…”
Section: Perfis Sensoriais Dos Vinhos 'Albariño' 2011 Em Relação Ao Tmentioning
confidence: 48%